2022
DOI: 10.1002/ajh.26531
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of COVID‐19 convalescent plasma with high titer antibody content by live viral neutralization assay is associated with modest clinical efficacy

Abstract: The efficacy of COVID‐19 convalescent plasma (CCP) as a treatment for hospitalized patients with COVID‐19 remains somewhat controversial; however, many studies have not evaluated CCP documented to have high neutralizing antibody titer by a highly accurate assay. To evaluate the correlation of the administration of CCP with titer determined by a live viral neutralization assay with 7‐ and 28‐day death rates during hospitalization, a total of 23 118 patients receiving a single unit of CCP were stratified into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
(141 reference statements)
0
8
0
Order By: Relevance
“… 100–103 As per the given limitations of available data as on August 2020 and the extent of outbreak and CCP usage under the expanded access protocol was escalated, and initial statistics on the potential efficacy of CCP were necessary to support the regulatory decision-making process. 104 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 100–103 As per the given limitations of available data as on August 2020 and the extent of outbreak and CCP usage under the expanded access protocol was escalated, and initial statistics on the potential efficacy of CCP were necessary to support the regulatory decision-making process. 104 …”
Section: Discussionmentioning
confidence: 99%
“…The case findings are as follows: the strengths of the analysis on early administration of CCP with high titer antibody content by live viral neutralization assay are associated with modest clinical efficacy, providing greater precision concerning CCP biologic activity and the power to detect modest treatment effects in the overall heterogeneous hospitalized population, reflecting real-world use of CCP in the early pandemic. 104 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several RCTs of CCP for treatment of moderate-to-severe hospitalized COVID-19 patients, typically at 7 or more days post-symptom-onset, did not find clinical benefits [ 8 , 9 , 16 22 ], although some trials found signals of clinical benefit, sometimes in certain subgroups [ 21 , 23 26 ]. Assessment of patients treated under the EAP found a modest survival benefit in patients who received high-titer CCP compared to those who received low-titer CCP [ 27 , 28 ]. A Bayesian reanalysis of RECOVERY argued that it remained plausible that CCP has a small but clinically significant effect on mortality in seronegative patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, three matched cohort studies 98,109,114 enrolling 330 participants and 12 case series 54,[134][135][136][137][138][139][140][141][142][143][144] enrolling 29,361 participants were included in this subgroup analysis. In this subgroup meta-analysis, treatment with COVID-19 convalescent plasma containing high antibody levels was associated with a 15% decrease in mortality rates compared to convalescent plasma containing low antibody levels, with a pooled risk ratio estimate of 0.85 (95% CI, 0.73 to 0.99).…”
Section: Subgroup Analysesmentioning
confidence: 99%